2018
DOI: 10.1007/s11356-018-2876-3
|View full text |Cite
|
Sign up to set email alerts
|

Nexus between financial development and CO2 emissions in Saudi Arabia: analyzing the role of globalization

Abstract: This study examines the contribution of financial development to environmental degradation in Saudi Arabia in the period from 1971 to 2016, controlling the model for globalization and electricity consumption. The autoregressive distributive lag (ARDL) and vector error correction methods (VECM) are applied to the long-run and causal relationship, respectively. Empirical results indicate that financial development contributes to CO emissions and degrades environmental quality. The results also show that the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
104
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 233 publications
(114 citation statements)
references
References 66 publications
9
104
1
Order By: Relevance
“…The study revealed that the long-run growth effect of FDI inflow on carbon emissions is quite large. Meanwhile, Yanchun [108] conducted a similar study in China found a significant negative impact of FDI on carbon emissions. Kim [56] investigates the relationship between carbon emissions, FDI, and energy consumption using a data of "Asian Newly Industrialized Countries (ANICS)".…”
Section: Literature Reviewmentioning
confidence: 96%
“…The study revealed that the long-run growth effect of FDI inflow on carbon emissions is quite large. Meanwhile, Yanchun [108] conducted a similar study in China found a significant negative impact of FDI on carbon emissions. Kim [56] investigates the relationship between carbon emissions, FDI, and energy consumption using a data of "Asian Newly Industrialized Countries (ANICS)".…”
Section: Literature Reviewmentioning
confidence: 96%
“…Future research could be conducted on a larger sample with more determinants of carbon for a different panel of countries. Similarly, the study may be enhanced by adding significant variables to the model, such as economic complexity (U. Shahzad, Z. Fareed et al 2020); COVID-19 role in air quality and pollution (F. Fareed et al 2020;Iqbal et al 2020), imported technology (Danish, Wang, and Wang 2018); financial development (Xu et al 2018) and information and telecommunication (Danish, Khan, et al 2018;Latif et al 2018). Further, future studies could extend this model with other economic and non-economic variables, such as forests, health outcomes, technology, etc.…”
Section: Concluding Remarks and Implicationsmentioning
confidence: 99%
“…Meanwhile, globalization facilitates financial sector reforms in both developing and developed countries, through which it can stimulate financial development and economic growth (Xu, Baloch, Meng, Zhang, & Mahmood, 2018). In the same way, financial development provides customers greater access to easy loans.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is hard for any single country to address energy and environmental challenges alone (International Energy Agency, 2019). Nevertheless, globalization also affects environmental quality through various channels (Xu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%